Capital constraints and risk shifting: An instrumental approach - Alejandro Drexler; Thomas B. King (Federal Reserve Bank of Chicago, 2021)
When firms approach distress, whether they engage in asset substitution (risk shifting) or rebuild equity (risk management) may depend on their access to capital markets. The property-casualty insurance industry has two features that make it ideal for testing this hypothesis: (1) the main losses for insurers are exogenous events like hurricanes that provide a strong instrument for financial distress; and (2) many insurers are organized as mutual companies, which cannot issue stock. Consistent with the importance of capital constraints, stock companies issue new equity following a negative shock, while mutual companies increase the riskiness of their investment portfolios.
Keywords: G22; G32; 330; Risk shifting; insurance; reinsurance; capital structure